Tinjauan Yuridis Terhadap Perkawinan Penghayat Kepercayaan menurut Undang-Undang Nomor 1 Tahun 1974 - Ranti Ranti; Ilham Abbas; Abdul Halim (Qawanin Jurnal Ilmu Hukum, 2021)
Abstract: This study aims to determine and analyze the legal status of the marriage ofpeople who believe in beliefs when viewed from Law Number 1 of 1974concerning Marriage and to determine and analyze the position of children bornfrom marriages of believers. This research is a research with a normativeapproach, where this method is a research that examines literature or documentstudies, using various legal materials such as legislation, court decisions, legaltheory and can be in the form of opinions of scholars. The technique of collectinglegal materials uses an in-depth marriage of believers according to the law. No. 1of 1974. The results of this study indicate that marriages of believers can be saidto be legal and marriages conducted before the Government Regulation No. 37 of2007 and have not been registered must be registered with the time limit givenuntil 2009 and meet the requirements in the form of a marriage certificate ofbelievers. , photocopy of ID card, photo of husband and wife, and/or passport ofhusband and/wife for foreigners. According to Government Regulation No. 37 of2007, the position of a child who believes in beliefs can be said to be legitimateand has a civil relationship with his parents, can also have a birth certificate orother administration like children in general. The recommendations of thisresearch encourage the public to be wiser and not consider anyone who does notfollow the six official religions recognized by the state as not believing in God,including atheists (or infidels), communists and so on. The government isresponsible as stated in Article 28I paragraph (4) of the 1945 Constitution of theRepublic of Indonesia to respect and protect the freedom of diversity. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis status hukumPerkawinan masyarakat penghayat kepercayaan jika dilihat dari Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan dan untuk mengetahui danmenganalisis kedudukan anak yang lahir dari perkawinan penghayatkepercayaan. Penelitian ini merupakan penelitian dengan pendekatan normatif,dimana metode ini merupakan penelitian yang mengkaji studi pustaka ataudokumen, yakni menggunakan berbagai bahan hukum seperti peraturanperundang-undangan, keputusan pengadilan, teori hukum dan dapat berupapendapat para sarjana. Teknik pengumpulan bahan hukum menggunakanpendalaman studi kepustakaan dari analisis hukum terhadap Perkawinanpenghayat kepercayaan menurut UU. No. 1 Tahun 1974. Hasil penelitian inimenunjukkan bahwa perkawinan penghayat kepercayaan dapat dikatakan sahdan perkawinan yang dilakukan sebelum adanya Peraturan Pemerintah No 37Tahun 2007 dan belum dicatatkan wajib untuk dicatatkan dengan batas waktuyang diberikan sampai pada tahun 2009 dan memenuhi persyaratan berupasurat perkawinan penghayat kepercayaan, foto kopi KTP, pas foto suami danistri, dan/atau paspor suami dan/istri bagi orang asing. Menurut PP No 37 Tahun 2007, kedudukan anak penghayat kepercayan dapat dikatakan sah danmemiliki hubungan keperdataan dengan kedua orangtuanya, juga dapatmemiliki akta kelahiran ataupun administrasi lainnya seperti anak padaumumnya. Rekomendasi penelitian ini mendorong agar masyarakat lebih bijakdan tidak menganggap siapapun yang tidak menganut enam agama resmi yangdiakui negara artinya tidak percaya Tuhan, termasuk atheis (atau kafir),komunis dan lain sebagainya. Pemerintah bertanggung jawab sebagaimana dipasal 28I ayat(4) UUD Negara Republik Indonesia Tahun 1945 untukmenghormati dan melindungi kebebasan beragama.